The Influence of Teacher Quality and Pedagogical Competence on Student Learning Outcomes at MTs Darunnajah Jakarta - Rokimin, Rokimin; Manaf, Sofwan (IJoIS: Indonesian Journal of Islamic Studies, 2024)
This study aims to determine the influence of teacher quality and pedagogical competence on student learning outcomes at Mts Darunnajah Jakarta. The method used is a quantitative approach with data collection through questionnaires distributed to 60 students. The results show that teacher quality (X1) has a significant influence on student learning outcomes (Y) with a contribution of 71%. Meanwhile, the pedagogical competence of teachers (X2) influences student learning outcomes by 66.1%. Simultaneously, the influence of teacher quality (X1) and pedagogical competence (X2) on student learning outcomes (Y) reaches 77.8%, based on the coefficient of determination, with the remaining 22.2% influenced by other factors. The implications of this study indicate that improving teacher quality and pedagogical competence is crucial for optimizing student learning outcomes and, therefore, should be a focal point in efforts to enhance educational quality in schools.